The Mongols and the Black Sea trade in the thirteenth and fourteenth centuries - Ciocîltan, Virgil (East Central and Eastern Europe in the Middle Ages, 450-1450,, 2012)
The inclusion of the Black Sea basin into the long-distance trade network – with its two axes of the Silk Road through the Golden Horde (Urgench-Sarai-Tana/Caffa) and the Spice Road through the Ilkhanate (Ormuz-Tabriz-Trebizond) – was the two Mongol states’ most important contribution to making the sea a “crossroads of international commerce”. The closest recorded working relationship between European and Asian powers in the medieval period, achieved by the joint efforts of the Chinggisid rulers and the Italian merchant republics, was not realised via the usual geographic channels of the Eastern Mediterranean and the Fertile Crescent, but rather by roundabout routes to the Black Sea. Thus at the same time as the sea fulfilled its function as a crossroads of long-distance Eurasian trade, it was also a bypass.